Karnaugh
$$ \renewcommand{\T}[1]{\mbox{#1}} \renewcommand{\Tb}[1]{{\bf \mbox{#1}}} \renewcommand{\F}[1]{\overline{\mbox{#1}}} \renewcommand{\Fb}[1]{\overline{{\bf \mbox{#1}}}} \newcommand{\AND}{\!\;\!\cdot\!\;\!} $$
MPOS
The following example assumes you were asked to construct the product-of-sums form for a three-input function $$\Tb{h}$$: $$\begin{align*} \Tb{h}(\T{A},\T{B},\T{C})= \F{A}\AND\F{B}\AND\F{C}&+ \F{A}\AND\F{B}\AND\T{C}+ \F{A}\AND\T{B}\AND\F{C}+ \F{A}\AND\T{B}\AND\T{C}+ \T{A}\AND\F{B}\AND\T{C}=\sum m(0, 1, 2, 3, 5) \end{align*}$$
you would proceed as follows:
- Determine the simplified function for the zeros - let's call it $$\Tb{g}$$. In this case, it turns out
$$\begin{align*} \Tb{g}=\Fb{h}=\F{A}\AND\T{C}+\T{B}\AND\T{C} \end{align*}$$
- Recognize that the function we are looking for is the opposite of $$\Tb{g}$$:
$$\begin{align*} \Tb{h}&=\Fb{g}\\ \Tb{h}&=\F{ $\F{A}\AND\T{C}+\T{B}\AND\T{C}$ } \end{align*}$$
- Use DeMorgan's Theorem $$(\F{$\T{x}+\T{y}$}=\F{x}\AND\F{y})$$ to rewrite the overall sum as a product:
$$\begin{align*} \Tb{h}=\F{$\F{A}\AND\T{C}+\T{B}\AND\T{C}$}&= \F{($\F{A}\AND\T{C}$)}\AND\F{$(\T{B}\AND\T{C})$} \end{align*}$$
- Again use DeMorgan's Theorem $$\left(\F{$\T{x}\AND\T{y}$}=\F{x}+\F{y}\right)$$ to rewrite the component products as sums:
$$ \begin{align*} \Tb{h}= \F{$(\F{A}\AND\T{C})$}\AND\F{$(\T{B}\AND\T{C})$}&= (\T{$\T{A}+\F{C}$})\AND (\T{$\F{B}+\F{C}$}) \end{align*} $$